2006
DOI: 10.1007/s10495-006-6303-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress regulated expression of Ubiquitin Carboxyl-terminal Hydrolase-L1: Role in cell survival

Abstract: The ubiquitin Carboxyl-terminal Hydrolase-L1 gene (UCHL1) is a key enzyme in the protein degradation pathway; however, its precise role in protecting cells under stress conditions is unclear. In the present study we investigated the activity of this gene in human NT2/D1 embryonal carcinoma cells subjected to oxygen-glucose deprivation (OGD) and reoxygenation. OGD/reoxygenation cause global metabolic changes due to energy withdrawal and the subsequent generation of reactive oxygen species which initiates either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 55 publications
(63 reference statements)
2
48
0
2
Order By: Relevance
“…Thus, one possible mechanism by which UCHL1 functions as tumor suppressor gene is through ubiquitinating oncoproteins and deubiquitinating tumor suppressor genes. Previous studies have shown that UCHL1 promotes the degradation of cell cycle inhibitor p27 kip1 (36,37) and stabilizes NF-κB (38) and p53 (12,19), but the specific substrates of UCHL1 in cancers are largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one possible mechanism by which UCHL1 functions as tumor suppressor gene is through ubiquitinating oncoproteins and deubiquitinating tumor suppressor genes. Previous studies have shown that UCHL1 promotes the degradation of cell cycle inhibitor p27 kip1 (36,37) and stabilizes NF-κB (38) and p53 (12,19), but the specific substrates of UCHL1 in cancers are largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Squares indicate the protein spots that were differentially expressed between sham and MCAO-operated groups. including cell differentiation, stress response, and apoptosis [21]. UCH-L1 attenuates neuronal cell death from oxidative stress, and a UCH-L1 decrease induces neuronal degeneration in neurodegenerative disease [5,21].…”
Section: Discussionmentioning
confidence: 99%
“…including cell differentiation, stress response, and apoptosis [21]. UCH-L1 attenuates neuronal cell death from oxidative stress, and a UCH-L1 decrease induces neuronal degeneration in neurodegenerative disease [5,21]. The reduction of UCH-L1 induces a malfunction of the de-ubiquitination and ubiquitination mechanisms, sequentially leading to apoptosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…When GAPDH was used as a control, no changes in TH and NET mRNA were found in the SG of mice 1 wk after ischemia-reperfusion (32). PGP9.5 gene expression can be downregulated by oxidative stress (41), and ROS generation is increased during ischemia-reperfusion injury (36) and can be induced by ANG II (49). The latter mechanism may contribute to the observed twofold decrease of PGP9.5 mRNA in the SG at 12 wk post-MI, since circulating plasma levels of ANG II are persistently elevated in rats post-MI (23).…”
Section: Time Course Of Th Net and Pgp95 Expressionmentioning
confidence: 99%